Numerical Simulation Study on Influencing Factors of Surrounding Rock Stability Based on AHP-Orthogonal Experiment Model - LI Lu (Renmin Zhujiang)
Taking the diversion tunnel of a hydropower station as an example,based on engineering and geological factors that affect surrounding rock stability,this paper considers elastic modulus E,cohesive force C,internal friction angle Φ,tunnel buried depth H,and tunnel radius R as influencing factors,carries out 16 sets of numerical simulation calculations under different working conditions with the principle of orthogonal experiment,and analyzes the vertical displacement at the top and the horizontal displacement at the waist of the tunnel by the range analysis and AHP method.The results show that:The primary and secondary factors affecting the vertical displacement at the top of the tunnel and their priorities are H>R>E>C>Φ,of which the weight is 43.097%,28.731%,19.117%,5.871%,3.184% respectively.The primary and secondary factors affecting the horizontal displacement at the waist of the tunnel and their priorities are H>E>R>C>Φ,of which the weight is 46.832%,21.820%,18.626%,8.160%,4.562% respectively.The combination of orthogonal range analysis and AHP method increases the satisfaction of consistency test,making the analysis results more reliable.